Money matters : an empirical research into the impact of government funding on Singapore’s Voluntary Welfare Organizations - Ng, Pei Qin (Nanyang Technological University, 2020)
This study sought to evaluate the impact of government funding on VWOs, specifically in the expansion of their programs and in improving the quality of services rendered to beneficiaries. Utilizing a mixed methods research design, we analyzed both the financial data of VWOs and interviewed 13 managers from different organizations across the sector. Analysis of our data revealed that while government grants facilitate the ramping up of organization capacity and increase the outreach of VWOs, organizations are overdependent on these funds. Despite this, the findings suggest that a collaborative government-VWO relationship in Singapore encourages VWOs to seek out private donors to be more self-reliant while expanding their operations further. From a policymaking perspective, an underlying challenge to maintaining this complementary relationship is the need to balance both accountability and transparency requirements for VWOs without compromising their effectiveness in serving and representing their clients.